Telepractice in Speech-Language Therapy During COVID-19 Pandemic - Rajput, Sabeen Iqbal (International Journal of Health, Medicine and Nursing Practice, 2023)
Objectives: The purpose of this paper is to review the recent literature and reflect on the studies conducted to investigate the efficacy of tele practice in speech-language therapy. This paper focuses more on the recent literature and the studies conducted during the coronavirus COVID-19 pandemic. Methodology: A review of the recent literature from 2012 to 2021 was studied on providing speech-language therapy intervention through tele practice. Key literature search sources included the Sci-hub, PubMed, HINARI (Health Inter Network Access to Research Initiative), and Google Scholar databases. Findings: The review of the literature provides evidence that telepractice delivery model for speech and language therapy services is an effective and useful way to cater to the needs of the patients. However, this paper also provides us with an insight that the hybrid model which is the combination of one-on-one and telepractice therapy session may be more effective and holistic way to provide therapy. There is a vital need for more investigative studies on the topic of telepractice. Unique Contribution to theory, practice, and policy: Speech and language therapist may opt for a hybrid therapeutic approach to achieve more functional outcomes. There is a need for in-depth and comprehensive investigative studies to fully understand the effectiveness of telepractice service delivery model when this model is utilized for variety of different speech and language disorder. Moreover, policies at professional institutes need to ensure that therapists undergo trainings on telepractice techniques and functionality to provide holistic treatment to patients and support care givers.